Prevention Of Sexual Exploitation On Migrant Young Girls’ In Sabah - Makanah, Herlina; Rahim, Rohani Abdul; Intung, Rovina; Landa, Azizah (Universiti Sains Malaysia, 2016)
Sabah is a destination and transit point for migrant workers, mainly from Indonesia, Bangladesh, the Philippines and other countries in Asia. Often their migration to Sabah in search of employment is done voluntarily. This includes the migrant young girls. Similar to women workers, the young girls being vulnerable, they were exposed to exploitation, cheating, misrepresentation by the employers and agents. They were trapped into debt bondage and forced labour by employers, employment agents or recruiters. Young girls are trapped, forced to work and perform work not suitable for their age and ability and paid less than adults doing similar work. These are common abusive, exploitative conducts practiced on these young girls. They were exploited and forced to pay various fees and their debts inflated to prolong exploitation particularly those smuggled into Sabah. The fact that they were exploited victims, this allows them to be protected under the Malaysia Anti- trafficking In Persons and Anti Smuggling Act 2007 (amendment 2012) as trafficked persons. It is most disastrous when it involves the sexual exploitation of migrant young girls by irresponsible syndicate, to gain profit from their vulnerability and ignorance. Thus, this paper intends to dwell into the problems faced by sexually exploited young migrant girls, types of exploitation and abuse faced, and protection conducted by the law enforcers to protect them and prevent such sexual exploitation by the local agents and employers.